Pengaruh Gaya Kepemimpinan Transformasional Terhadap Komitmen Organisasional Dan Organizational Citizenship Behavior Yang Dimediasi Oleh Kepuasan Kerja - supit, Isa Yohannes Israel (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
Recently the growing of the hospital as the healthy services organization is increasing rapidly. This raises an intense competition between hospitals. Hospital not only compete each other but also with a practical tocologist, practical doctors and other healty services. The result of the research show that leadership transformation is significantly effect te job satisfaction. Leadership transformation is significantly effect the OCB. Job satisfaction issignificantly effect the organization commitment. Organization commitment is significantly effect the OCBKeywords: Transformation Leadership style, organization commitment, OCB, job satisfaction